If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7x + -12 = 144 Reorder the terms: -12 + 5x + 7x = 144 Combine like terms: 5x + 7x = 12x -12 + 12x = 144 Solving -12 + 12x = 144 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 12x = 144 + 12 Combine like terms: -12 + 12 = 0 0 + 12x = 144 + 12 12x = 144 + 12 Combine like terms: 144 + 12 = 156 12x = 156 Divide each side by '12'. x = 13 Simplifying x = 13
| 7x^2+31x-38=0 | | x^2+x-0.01=0 | | 7x^2+3x+3x+4=-3x+5 | | 2x/-3x=2 | | 4x^2-2x=px^2+2x+3 | | 7x=8x-15 | | 6x-3=10x+5 | | (2x^2-7x+3)(2x^2-x+3)+8x^2=0 | | 5x=40+3 | | -16=-5+2(2-m) | | 2x=19/6 | | 204=2y+y | | 5(x+3)+x=4(x+5)+3 | | 2x+80-4x=50 | | x(x/3)=12 | | x(x/3) | | x*x/3 | | 9x+2(60)=7x+7(60) | | c=120+.65y | | (2a-3)(4a^2+6a+9)=0 | | 2y+5y(2-y)=3-5y | | x(3x)=8 | | x^2-6x+y=0 | | x^3-4x^2+5x+2=0 | | cos(4*x-(pi))=-0.5 | | -2-3x=4x | | 2x^2+mx-3=0 | | 3X-18=-4 | | 13-6(x-16)=-33 | | 5+(-4x-26)=8 | | 3x^2+4=130 | | 32x-14x=10 |